Las aspiraciones de Silvio Astier: Fama, delito y lectura en El juguete rabioso de Roberto Arlt - Canala, Juan Pablo (Centro de Estudios de Teoría y Crítica Literaria, IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. UNLP, 2011)
The present work aims at studying Roberto Arlt?s El juguete rabioso from the perspective of genetic criticism, according special importance to the systematic analysis of Arlt's various types of preparatory sketches of the novel, which were published in literary magazines as previews of an upcoming work. The aspects developed here invite reflection on the connections between avant-textes and text as a starting point to study the literary work; their main purpose is to observe the different changes experienced by Silvio Astier along the successive writing stages. Arlt's unsteady representations of Astier concerning reading and the universe of books will be especially noted, as well as considerations regarding the idea of literary recognition and the role of crime